New cascade boost converter with reduced losses. Issue 6 (1st May 2016) - Lotfi Nejad, Mohammad; Poorali, Behzad; Adib, Ehsan; Motie Birjandi, Ali Akbar
Abstract : To enhance the gain of conventional boost converters in applications such as fuel cells and photovoltaic systems, cascade boost converters are normally applied. In this study, a new cascade boost converter topology with reduced conduction losses is proposed. This converter shows reduced root‐mean‐square currents of the circuit elements and reduced conduction losses. The proposed converter is analysed and compared with the conventional circuit topology. The proposed converter has all the advantages of cascade boost converter with the advantage of reduced conduction losses. Finally, simulation and experimental results of a 200 W laboratory prototype are presented.